To match the equations on the left with their equivalent forms on the right, we need to identify which quadratic expressions are equivalent to one another.
Here’s the comparison for the given equations:
-
y = x² + 6x + 5
- This can be factored to:
- y = (x + 1)(x + 5)
- It does not match any of the forms provided on the right.
- This can be factored to:
-
y = (x - 3)² + 4
- Expanding this gives:
- y = (x² - 6x + 9) + 4
- y = x² - 6x + 13
- This does not match any of the forms provided on the left.
- Expanding this gives:
-
y = x² - 5x + 6
- This can be factored as:
- y = (x - 2)(x - 3)
- It does not match any of the specific forms provided on the right.
- This can be factored as:
Based on this analysis, the original three equations do not have matching pairs in the responses you provided. If additional options or clarifications are available, please share them for more accurate comparisons.